Thermochronology of the South American platform in the state of São Paulo, Brazil, through apatite fission tracks - Saenz, CAT; Hadler, J. C.; Iunes, P. J.; Guedes, S.; Hackspacher, P. C.; Ribeiro, LFB; Paulo, SR; Osorio, AMA (Elsevier B.V., 2005)
The fission-track method (FTM) in apatite was applied to 45 samples collected in the Serra da Mantiqueira (Mantiqueira mountain range), the Serra do Mar (Mar mountain range), regions next to these mountain ranges and the coastal region between Ubatuba and Santos in the State of São Paulo, Brazil, to study the thermochronology of the South American Platform in southeast Brazil and its influence on Santos and Campos basins. The data presented in this work complement the previously presented data on the same region (Tello Saenz et al., 2003. J. S. Am. Earth Sci. 15, 765-774) with 31 new samples analyzed. The weighted mean of the corrected ages from high Mantiqueira (around 1000 m), (121 +/- 6) Ma, coincides with the South Atlantic opening. The fact that its thermal history starts at a relatively low temperature (similar to 80 degrees C) suggests that the age of similar to 120 Ma would be the formation age of Serra da Mantiqueira due to a rapid pulse, in which tracks had no time to be retained at the closure temperature, that is similar to 120 degrees C. The Serra do Mar presents a more complicated thermal history, with several reactivations indicated by the changes in the slope of its cooling curve. The thermal histories obtained in the regions next to these mountain ranges are compatible with the results mentioned above. The Santos Basin has unconformities that agree with changes in the slope thermal histories of the studied region. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: fission-track analysis; thermochronology; thermal histories; apatite; southeast Brazil